Characteristics of In2G Variant in Congenital Adrenal Hyperplasia Due to 21-Hydroxylase Deficiency - Kocova, Mirjana; Concolino, Paola; Falhammar, Henrik (Frontiers in Endocrinology, 2022)
Substantial research has been performed during the last decades on the clinical and genetic variability of congenital adrenal hyperplasia (CAH) and its most common form, 21-hydroxylase deficiency (21OHD). CAH is one of the most prevalent autosomal recessive diseases in humans, and it can be divided into classic—further subdivided into salt wasting (SW) and simple virilizing (SV)—and non-classic (NC) forms. Pathogenic variants of CYP21A2 gene, encoding the 21-hydroxylase enzyme, have been reported with variable prevalence in different populations. NM_000500.9:c.293-13C/A>G (In2G) variant represents the most common CYP21A2 gene changes related to the classic 21OHD form. However, the phenotype of In2G carriers is variable depending on the variant homozygous/heterozygous status and combination with other CYP21A2 pathogenic variants. In addition, identical genotypes, harboring the homozygous In2G variant, can present with variable phenotypes including the SW and SV or rarely NC form of the disease. Here, we analyze and present the clinical aspects, genotype/phenotype correlations, and other characteristics related to the CYP21A2 In2G variant.